A correlation between in vivo and in vitro effects of the microtubule inhibitors colchicine, parbendazole and nocodazole on myxamoebae of Physarum polycephalum. - Quinlan, R; Roobol, A; Pogson, C; Gull, K (1981)
The effects of the microtubule inhibitors colchicine, parbendazole and nocodazole on the growth of myxamoebae of Physarum polycephalum were closely paralleled by the effects of these drugs on the assembly in vitro of purified amoebal microtubule protein. Colchicine at 100 microM did not inhibit amoebal growth and did not inhibit formation, or depolymerization, of amoebal microtubules. The benzimidazole carbamate derivatives nocodazole and parbendazole were very effective in both inhibiting growth and inhibiting the assembly in vitro of amoebal microtubule protein. Parbendazole was the most effective.